Analysis of juglone concentrations in walnut shells and woods - Zatil Afrah Athaillah; Xueqi Li; Selina C. Wang (Cogent Food & Agriculture)
Juglone is a quinone that has been associated with both deleterious environmental effects and potential health benefits, depending on the concentrations. At high concentrations, juglone can limit the growth of some plants and exert toxic responses on some animals. At low concentrations, juglone is safe and even fosters positive effects, e.g. reduces cancer cell growth. Therefore, determining the concentration of juglone in walnut industry byproducts, particularly shells and wood chips, is important to help evaluate their safety and utility to be used as value-added products. In this work, we optimized the juglone extraction procedure and quantitative analytical method via liquid chromatography. Three solvents (methanol, aqueous acetone, and chloroform) were compared. Methanol performed effectively for wood chips, and aqueous acetone was the optimum solvent for shells. Our data showed that juglone concentration in black walnut shells (0.45 ± 0.12 µg/g db) was similar to that in English walnut shells (0.74 – 1.70 µg/g db). Juglone concentrations in wood chips were 28.84 ± 1.54 and 65.50 ± 2.13 µg/g db for English and black walnuts, respectively. Shells and wood chips were considered safe because their juglone concentrations were lower than the level that adversely affects some animals and plants.